ANALYSIS OF DISTRICT RULES OF KOTA BOGOR CITY NUMBER 10 YEARS 2021 ON HARASSMENT AND COMBATING SEXUAL DEVIANT BEHAVIOR - Najwa Havita, Deandra; Aridhayandi, M. Rendi (DE'RECHTSSTAAT, 2024)
Western culture is not in accordance with the laws and norms that apply in Indonesia, especially the city of Bogor. The community participated to be able to influence government policy through mass demonstrations that occurred in 2018, to stop the spread of sexual deviant behavior such as harassment and LGBT. The aim of this research is to find out how Bogor City Regional Regulation Number 10 of 2021 can regulate harassment and combat sexual deviant behavior. This research methodology uses a qualitative research approach where qualitative research as a scientific method is often used and carried out by a group of researchers in the field of social sciences, including law. The research results show that this regulation contains articles that result in the law not being based on evidence-based policies. According to ICD-10 (International Classification of Disease) or the Health classification made by WHO (World Health Organization) states in point F66 that "sexual orientation itself should not be considered a disorder" and the ICD also states that transgender is not a mental disorder. All forms of deviation mentioned in this regulation in article 6 are crimes that do not cause victims. Crimes are evil acts that must cause victims and the victim is someone else and not oneself who is the victim. So it cannot be said to be a crime. If it is said that sexual deviation is behavior that is not consensual or involves violence, then this can only be said to be sexual deviant behavior, but apart from sexual deviation that is carried out with consent and in the private sphere, then this is an element of violence. privacy that the state has the right to protect and everyone has the right to their own privacy.